N-acetylcysteine as a promising treatment for COVID-19: A comprehensive meta-analysis of systemic manifestations and clinical outcomes - S. Saleh, Helmy; B. Zaid, Ahmed; K. Almahdy, Shaimaa; M. Elmalawany, Alshimaa; Abdeen, Ahmed; Alsaati, Ilhaam; F. Ibrahim, Samah (Italian Journal of Food Science, 2025)
The COVID-19 pandemic presents systemic disorders, primarily affecting respiratory and cardiovascular systems. N-acetylcysteine (NAC) possesses antioxidative, anti-inflammatory, and immune-modulating properties, suggest-ing a potential therapy against COVID-19. In the current study, a meta-analysis was conducted to investigate the effectiveness of NAC supplementation against COVID-19. A literature search was conducted from April 2019 to December 2023 using Rev-Man 5.3 incorporating 14 studies with 20,980 participants. Results revealed significant differences in total and native thiol, and hydrogen sulfides in COVID-19 patients. NAC-treated patients exhibited significant reduction in C-reactive protein and D-dimer levels, along with higher pO2/FiO2 ratios, minimal stay in hospital, and lower mortalities supporting the efficacy of NAC toward COVID-19.